2003
DOI: 10.1039/b209779f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the competitive rate of derivatization of several secondary amines with phenylisocyanate (PHI), hexamethylene-1,6-diisocyanate (HDI), 4,4′-methylenebis(phenyl isocyanate) (MDI) and toluene diisocyanate (TDI) in liquid medium

Abstract: The stabilization of the isocyanate (NCO) groups during workplace sampling is necessary for their subsequent laboratory analysis. Most derivatization reagents are secondary amines. By carrying out a test in which two secondary amines are added to an isocyanate, the relative rates of these reactions can be evaluated. This evaluation is known for a monoisocyanate, phenylisocyanate (PHI), but is being developed for diisocyanates. This study deals with the relative reactivity (RR) of four diisocyanates: hexamethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The reason for this is steric hindrance. 24 Here, LDI shows a higher reactivity for the isocyanate closest to the methyl ester substituent despite the expected steric hindrance. This could be explained by the fact that the ester group is an electronwithdrawing group, which would lead to an increase in the nucleophilicity of the isocyanate.…”
Section: Resultsmentioning
confidence: 94%
“…The reason for this is steric hindrance. 24 Here, LDI shows a higher reactivity for the isocyanate closest to the methyl ester substituent despite the expected steric hindrance. This could be explained by the fact that the ester group is an electronwithdrawing group, which would lead to an increase in the nucleophilicity of the isocyanate.…”
Section: Resultsmentioning
confidence: 94%
“…(5) Common derivatizing agents include tryptamine, 1-(2-methoxyphenyl) piperazine (MOPP), and 1-(9-anthracenylmethyl) piperazine (MAP) as listed in the NIOSH Manual of Analytical Methods for isocyanates; 9-(methylaminomethyl) anthracene (MAMA), which is used in the SKC Inc. Iso-Chek method; and, 1-(2-pyridyl) piperzine (1-2PP) as used in OSHA Method 47 for MDI. (26)(27)(28)(29) Tremblay et al (30) investigated competitive rates of derivatization of several secondary amines and isocyanates. Relative differences were observed in MDI reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…A typical synthesis scheme of PU prepolymer is shown in Figure A. Previous work had shown that the isocyanate group at position 4 was more reactive than that at position 2 (adjacent to the methyl group, only ≈12% of the reactivity of position 4) on the asymmetric TDI . Thus, we assumed that most of the hydroxyl groups of L‐PEG and F‐PCL reacted with the isocyanate group at position 4 and the structure shown in Figure A represented the majority components of the resultant prepolymer.…”
Section: Resultsmentioning
confidence: 99%